МАТЕРИАЛЫ СУРСКОЙ КУЛЬТУРЫ С ПОСЕЛЕНИЯ ВОВЧОК (Zaporizhzhia Historical Review, 2021)
The ceramics of the Surskaya culture from the Vovchok settlement are considered in the article. This settlement was excavated by А.V. Dobrovolsky in 1929. Its materials are not published till now. They are kept at the National Museum of History of Ukraine in Kyev. The collection of the Surskaya pottery includes fragments from 38 vessels. They are made of clay with various impurity, ornamented by strokes, drawn lines and prints of short comb. This materials are referred to the third period of the Surskaya culture and date about 5650-5200 ВС.